Notary's Responsibility for Errors in the Authentic Deed Making Process - Yuhana, Shaza Refa; Hanim, Lathifah; Gunarto, Gunarto (Jurnal Konstatering, 2025)
Abstract. This study aims to analyze the notary's responsibility for errors in the process of making authentic deeds based on Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary. This study uses a sociological juridical approach with descriptive analytical research specifications, using primary and secondary data collected through literature studies and interviews, then analyzed qualitatively. Based on the study, it is concluded that notaries have legal responsibilities that include civil, criminal, and administrative aspects when errors occur in the process of making authentic deeds. Errors can be categorized into five types, namely errors related to the parties present, the object of the deed, the content of the deed, the formality of the deed, and the notary protocol. The legal implications of these errors can result in the deed being canceled, null and void, or only having evidentiary force as a private deed. The analysis of the case of the High Court Decision Number 166/PDT/2018/PT YYK shows that a simulated deed can be declared null and void and provides legal certainty. Error prevention can be done through a thorough understanding of the regulations, caution, thoroughness in carrying out duties, and proper notary protocol keeping.